An Updated Review on Complicated Mechanisms of COVID-19 Pathogenesis and Therapy: Direct Viral Damage, Renin-angiotensin System Dysregulation, Immune System Derangements, and Endothelial Dysfunction - Falahi, Shahab; Maleki, Maryam; Kenarkoohi, Azra (Infectious Disorders - Drug Targets, 2022)
SARS-CoV-2 was reported as the cause of coronavirus disease 2019 (COVID-19) in late December 2019. According to sequencing and phylogenetic studies, the new virus belongs to Coronaviridae family and Betacoronavirus genus. Genomic sequence analysis has shown SARS-CoV-2 to be similar to SARS. SARS-CoV-2 is more infectious, and the high level of COVID-19 community transmission has led to a growing pandemic. Although infections in most patients with COVID-19 are moderate or mild, 20% of the patients develop a severe or critical form of the disease. COVID-19 may affect a wide range of organs and tissues, including the respiratory system, digestive system, nervous system, and skin. Patients with COVID-19 have been confirmed to have renal, cardiovascular, gastrointestinal, and nervous system problems in addition to pulmonary involvement. The pathogenesis of SARS-CoV-2 is being investigated, but it is possible that the organ damage might in part be caused by direct viral damage (detection of inclusion bodies in tissues, such as the kidneys), dysregulation of the immune system, renin-angiotensin system, bradykinin pathway, and coagulation, as well as host genetic factors and their polymorphisms, which may affect the disease severity. In this review, an update on the possible pathogenesis pathways of COVID-19 has been provided. It is hoped that the best care strategy will be developed for patients with COVID-19 by identifying its pathogenesis pathways.
Keywords: Renin-angiotensin system